Efficient Inequity-Averse Teams - Jianpei Li (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2007)
This paper analyzes the efficiency of team production when agents exhibit other regarding preferences. It is shown that full efficiency can be sustained as an equilibrium through a budget-balancing mechanism that punishes some randomly chosen agents if output falls short of efficient level but distributes the output equally otherwise, provided that the agents are sufficiently inequity averse.
urn:nbn:de:bvb:19-epub-13342-9
Keywords: C7; D7; D63; L2; 330; moral hazard; team production; inequity aversion